Image–Music–Text: Operatic Experiments in the Age of the Audiovisual Essay - João Ricardo (INSAM)
Emerging as a new tool and form of criticism and theorizing, the audiovisual essay has stirred many different opinions within the academy, with its many different outcomes. For scholarly purposes, combining it with text, reflection and commentary seems to be the most common and most accepted form of audiovisual essay, easily found all over the internet in wellknown video archives such as YouTube and Vimeo. Towards a more poetic end of the spectrum, breaking both the horizontal and vertical dimensions of any work may deepen and reveal new possibilities, often resulting in the creation of new hybrid pieces. This paper aims to demystify these new formats and concepts, focusing on its potentiality as a tool for criticism and its creative possibilities regarding music and, more specifically, opera.